Aberrant driving behaviours among ride-hailing drivers: direct and indirect effects of personal attributes and work-condition factors. Issue 3 (4th May 2022) - Shi, Jing; Hussain, Muhammad; Peng, Dandan
Abstract: In recent years, due to the prevalence of road crashes among ride-hailing drivers in China, the investigation of aberrant driving behaviours of ride-hailing drivers has become indispensable. This paper aims to estimate the direct and indirect effects of personal attribute and work-condition factors on aberrant driving behaviours (driver distraction and other aberrant driving behaviours) of ride-hailing drivers in China. The study utilises a self-reported questionnaire survey data of 420 Chinese ride-hailing drivers and constructs a Structural Equation Model (SEM). The results of the model demonstrate that: (1) the gender, income, driving style, and work-condition factors are the significant predictors of aberrant driving behaviours of ride-hailing drivers; (2) work-condition factors and income has a direct effect on driver distraction and other aberrant driving behaviours; (3) driving style is an important factor negatively effecting other aberrant driving behaviours; (4) gender and work-condition factors has indirect effects on driver distraction and other aberrant driving behaviour, mediated by driving attitude. The results reveal that ride-hailing drivers having higher-income, high competition pressure, and online reward systems in the industry are directly associated with more aberrant driving behaviours. This study would help government agencies and policymakers improve road safety by keeping in mind the aberrant driving behaviours of ride-hailing driving.